Waste disposal in the Netherlands as reflected in shipwrecks of the former Zuiderzee - van Holk , André; Overmeer, Alice (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In 2019 a shipwreck in the Netherlands was re-excavated as part of a training project for archaeology students and volunteers. It was the wreck of a 19th-century pram-like vessel, loaded with a cargo of what seemed to be household waste. However, analysis of the cargo composition showed a different picture. Based on the specialists’ investigations it can be stated that the ship’s cargo consisted of various components. These can be traced back to different batches of waste, each of which has its own origin. A part of the cargo consisted of household waste, originating from one or a few reasonably affluent households. A second part comprised construction and demolition waste from an urban context. A third component consisted of industrial waste derived from coal gas production. This find may shift the prevailing picture of waste disposal and transport in the Netherlands.